Contraceptive User’s Profile - Gunardi, Eka R (Indonesian Socety of Obstetrics and Gynecology, 2013)
Objective: To obtain informations regarding the profile of contraceptive users in Raden Saleh Clinic, Jakarta. Method: A cross-sectional study was conducted in June 2012, at Raden Saleh Clinic, Jakarta. The study population was the patient who came to Raden Saleh Clinic from 2008 until 2011. Results: The mean age of the contraception users was 34.06 and the mean of their husband’s age was 38.91 years old. Most of the patients were graduated from senior high school (43.2%) and university (37.9%). More than half of the patients (55.2%) were not working and more than a half of their husband (53.2%) were private employee. Almost all (92.6%) of the patient were married. Most of the patient (38.8%) came with no prior contraception. After consultation, all patients had chosen their preferred contraceptive methods, namely IUD (61.4%), injectable contraception (20.9%), pill (13.7%), sterilization (3.4%), and implant (0.6%). Conclusion: Family planning reduces maternal mortality and the best method is different for each patient because of the difference in their own condition and the consideration of the cost and benefit. [Indones J Obstet Gynecol 2013; 1-4:179-82] Keywords: contraception, contraceptive users profile